2013
DOI: 10.1111/phpp.12016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum 25‐hydroxyvitamin D levels in vitiligo patients with and without autoimmune diseases

Abstract: Deficient serum 25(OH)D levels are present in vitiligo patients with and without systemic autoimmune diseases. Accordingly, screening for vitamin D deficiency seems of value in vitiligo patients for the possibility of vitamin D supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 23 publications
(47 reference statements)
6
71
1
1
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20] There was no significant decrease in vitamin D levels in patients with associated autoimmune comorbidity in our study. Similar results have been found by Khurrum et al, Saleh et al as well as Beheshti et al 7,18,19 All other studies had found a significant decrease in vitamin D levels in patients having comorbid autoimmune conditions. 12-20, Further studies having a larger sample size may reveal a correlation in the Indian context.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18][19][20] There was no significant decrease in vitamin D levels in patients with associated autoimmune comorbidity in our study. Similar results have been found by Khurrum et al, Saleh et al as well as Beheshti et al 7,18,19 All other studies had found a significant decrease in vitamin D levels in patients having comorbid autoimmune conditions. 12-20, Further studies having a larger sample size may reveal a correlation in the Indian context.…”
Section: Discussionsupporting
confidence: 80%
“…Similar results were obtained in a study by Finamor et al as well as Takczi et al 9,11 However the majority of patients in other studies had a mean age below 35. [6][7][8][12][13][14][15][16][17][18][19][20] This may reflect certain social attitudes towards the disease i.e. hesitancy to consult local physicians regarding vitiligo, or presenting to a tertiary center only after prolonged native treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few studies evaluating serum vitamin D levels in vitiligo patients [9, 10]. Ustun et al .…”
Section: Discussionmentioning
confidence: 99%
“…Significantly lower serum vitamin D levels were seen in the patients relative to controls. The authors speculated on the possibility of vitamin D supplementation for the treatment of vitiligo patients in the future [10]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation